Approaches for the Detection of Escherichia coli in Wastewater: A Short Review. Issue 13 (3rd April 2023) - Zulu, Nokwanda; Idris, Azeez O.; Orimolade, Benjamin O.; Nkambule, Thabo T. I.; Mamba, Bhekie B.; Feleni, Usisipho
Abstract: Escherichia coli is a harmful pathogenic bacterial species causing serious intestinal sickness in humans. This bacterium has been linked to contaminated epidemics that have led to significant mortality and morbidity across the world. E. coli, like most other waterborne infections, is tricky to discover effectively in the water supply. Therefore, there is a demand for advanced E. coli detection methods that can sensitively and rapidly detect these pathogens. This review reveals several approaches used for the detection of E. coli bacteria using conventional methods such as multiple tube fermentation and membrane filtration techniques. The emerging approaches give quite accurate and speedy identification despite the necessity for culturing; nevertheless, they lack precision and necessitate extra lab testing. Because analytical techniques such as GC‐DMS lack specificity, the invention of a sensing device that is simple to use, compact, extremely sensitive, and specific has proven essential in identifying incredibly low concentrations of harmful E. coli in drinking water. Abstract : This review reveals several approaches used for the detection of E. coli bacteria using conventional methods such as multiple tube fermentation and membrane filtration techniques. The emerging approaches give quite accurate and speedy identification.